DRAMATURGY OF SUNDANESE CULTURE-BASED POLITICAL COMMUNICATION IN THE CONSTRUCTION OF SOCIAL MEDIA HYPERREALITY - Fauzie Hikmatussalam Sutrisna (RADJA PUBLIKA, 2026)
This research aims to analyze how Sundanese culture-based political communication is constructed through social media to form a political hyperreality in the midst of West Java society. The research uses a qualitative approach with dramaturgical analysis methods from Erving Goffman and hyperreality theory from Jean Baudrillard. Social media is no longer just a space for political communication, but has turned into a stage for symbolic performances that display images of closeness, simplicity, religiosity, and local cultural identity. Sundanese culture is used as a symbolic instrument to build political legitimacy through emotional and populist digital visualization. Research has found that local culture-based political content on social media tends to produce simulated realities that the public consumes as socio-political truth. In these conditions, the boundary between political reality and digital imagery becomes blurred. The dramaturgy of digital politics finally gives birth to hyperreality, which is a situation when media representations are more reliable than empirical reality in the field.